BLDC motor output feedback velocity tracking control with trapezoidal approximation and no angular velocity state observer - Guerrero, Cuauhtémoc; Santibanez, Victor; Villalobos-Chin, Jorge; Orrante-Sakanassi, Jorge; Ollervides, Javier (Zielona Góra: Uniwersytet Zielonogórski)
In this work, a velocity tracking control strategy is presented using passivity methodology for a permanent magnet synchronous machine with uniformly distributed windings, which is known as a brushless direct current (BLDC) motor. The trapezoidal components of back electromotive force (EMF) are here modeled by using a novel differentiable approximation.
Keywords: BLDC motor; partial stability; second-order filter; trapezoidal approximation